The Effects of Team Mental Model Complexity on Team Information Search and Performance Trajectories. Issue 3 (June 2023) - Uitdewilligen, Sjir; Waller, Mary J.; Roe, Robert A.; Bollen, Peter
Drawing on the concept of requisite complexity, we propose that mental model complexity is crucial for teams to thrive in dynamic complex environments. Using a longitudinal research design, we examined the influence of team mental model complexity on team information search and performance trajectories in a sample of 64 teams competing in a business strategy simulation over time. We found that team information search positively influences performance growth over time. More specifically, and consistent with requisite complexity, we found that mental model complexity positively influences both performance growth and information search over time, above and beyond the effects of mental model similarity and accuracy.